Increased peripheral blood leukocyte subsets with regulatory phenotype in clinically stable long-term HIV-infected hemophilia patients on HAART may be beneficial and contribute to a decrease in autoimmunity - Daniel, Volker; Naujokat, Cord; Sadeghi, Mahmoud; Zimmermann, Rainer; Huth-Kühne, Angela; Opelz, Gerhard (Viral immunology, 2010)
After initiation of highly-active antiretroviral therapy (HAART), long-term HIV-infected hemophilia patients have been shown to lose autoantibodies against CD4(+) peripheral blood leukocytes (PBL), suggesting that HAART induces autoimmunity-blocking mechanisms. We compared cytokine levels and subpopulations of lymphocytes and dendritic cells (DC) in the blood of 40 long-term HIV(+) patients with those of 13 long-term HIV(-) hemophilia patients; 23 HIV(+) patients had a detectable retroviral load. Cell subsets were determined using flow cytometry and cytokine levels were measured using ELISA. HIV(+) patients showed higher proportions of DC subpopulations with immunostimulatory phenotypes (p < 0.01), CD8(+) PBL (p < 0.001), and IL-2 (p < 0.001) and sIL-2R plasma levels (p = 0.002) than HIV(-) patients. They also exhibited increased proportions of T PBL with immunosuppressive phenotypes such as CD3(+)CD4(+)CD25(+)Foxp3(+) (p = 0.001), and CD3(+)CD8(+)CD28(-)Foxp3(+) PBL (p < 0.001), and a decreased IL-7R expression on CD3(+)CD8(+) PBL (p = 0.001) compared to HIV(-) patients. Frequencies of CD3(+)CD4(+)CD25(+) PBL producing IL-2, IL-4, IL-10, IL-12, and/or IFN-gamma, and of CD3(+)CD4(+)CD28(-) PBL secreting IL-2 and/or IL-4 were lower in HIV(+) than in HIV(-) patients (p <or= 0.02). Proportions of CD4(+) PBL coated with IgG, IgM, and C3d were similar in HIV(+) and HIV(-) patients (p = n.s.). However, the proportion of CD4(+)gp120(+) PBL was higher in HIV(+) patients (p = 0.002), and associated with low CD3(+)CD4(+)CD25(+)Foxp3(+) PBL (p = 0.012). We conclude that long-term HIV-infected hemophilia patients on HAART show an adaptive immune response, presumably against HIV, in the presence of upregulated immunosuppressive T PBL, downregulated cytokine-producing CD4(+) PBL, and downregulated IL-7R expression on CD8(+) PBL. Increased immunoregulatory T PBL might decrease autoimmunity, thereby contributing to immunological reconstitution and stabilization of long-term HIV-infected hemophilia patients on HAART.